The interrelation between hardness and compressibility of substances and their structure and thermodynamic properties - Mukhanov, V. A.; Kurakevych, O. O.; Solozhenko, V. L. (Journal of superhard materials, 2008)
A strong correlation relationship has been established between the structure and specific Gibbs free energy of the substance atomization on the one hand, and the substance hardness and volume compressibility on the other. In the framework of the model proposed hardness is directly proportional to the specific Gibbs free energy per bond in isodesmic crystals. An application of a correction coefficient to the ionic component of chemical bonds allows one to evaluate the hardness of compounds having both the covalent (polar and nonpolar) and ion bonds. In the framework of the suggested approach we have been the first to correctly calculate the temperature dependence of the hardness by the example for diamond and cubic boron nitride.